Analytical study on ethical issues in events - voices from Muslim organizers - Fatah Yasin, Mohammad Dhiya’ul Hafidh; Fatah Yasin, Raudlotul Firdaus (2023)
In the realm of education, ethics represents a crucial component within MQF 2.0, whereas ethical considerations in event management pertain to the United Nations' Sustainable Development Goals spanning from 6th to 15th. 1400 years ago, Prophet Muhammad (PBUH) informed his followers that virtuous mer-chants would be among those who join him in Paradise. Ethics permeate every aspect of human existence, often presenting challenges. The present study seeks to identify ethical quandaries within the event management industry and propose solutions through snowball sampling methodology employing open-ended ques-tions. However, it is limited in scope to the perspectives of Muslim organiz-ers.The study was confined to the domain of Islamic hospitality that is compliant with Muslim-friendly standards. The survey culminated in six participants who brought attention to various concerns such as ikhtilat, waste management, impar-tiality, religious and racial sensitivity, unprofessional conduct during Q&A ses-sions, and deficient administration.The study has determined that each issue has been thoroughly discussed in both Islamic and conventional research, with de-tailed analysis. These findings provide a valuable foundation for further research comprising a wider range of respondents. Moreover, the results encourage indus-try players to enhance their services for Muslim markets while remaining faithful to Islamic values.